The job creation effect of R&D expenditures - Francesco Bogliacino; Marco Vivarelli (European Commission, Joint Research Centre (JRC), 2010)
In this study we use a unique database covering 25 manufacturing and service sectors for 15 European countries over the period 1996-2005, for a total of 2,295 observations, and apply GMM-SYS panel estimations of a demand-for-labour equation augmented with technology. We find that R&D expenditures -fostering product innovation- have a job-creating effect, in accordance with the previous theoretical and empirical literature discussed in the paper. Interestingly enough, the labour-friendly nature of R&D emerges in both the flow and the stock specifications. These findings provide further justification for the European Lisbon-Barcelona targets.
Keywords: O33; 330; Technological change; corporate R&D; employment; product innovation; GMM-SYS